Crystallization Behaviour of MgB2 Films Fabricated on Different Cathodes via Electrochemical Technique - Yang, Huazhe; Yu, Xiaoming; Sun, Xiaguang; Ji, Yang; Qi, Yang (Asian Journal of Chemistry, 2012)
An electrochemical technique has been devised and settled to fabricate superconducting MgB2 films in molten salts. MgCl2, Mg(BO2)2, NaCl and KCl were used as electrolyte, graphite was used as anode and graphite and stainless steel were chosen as cathode, respectively. In the process of electrolysis, MgB2 films were fabricated under Ar-gas flow. X-ray diffraction analysis was adopted to investigate the phase composition and crystallization property of the films. The results indicate that MgB2 films have been fabricated successfully on different cathodes and the optimized electrolysis temperature are 620 ºC for graphite and 606 ºC for stainless steel. Furthermore, pulse power supply can enhance the content of MgB2 phase.